2020
DOI: 10.1163/22941932-bja10007
|View full text |Cite
|
Sign up to set email alerts
|

Cambial phenology in Abies pindrow (Pinaceae) along an altitudinal gradient in northwestern Himalaya

Abstract: Climate change is expected to be heterogeneous across the world, with high impacts on the Himalayan ecosystems. There is a need to precisely document cambial phenology and wood formation in these regions to better understand climate-growth relationships and how trees face a warming climate. This study describes the dynamics of cambial phenology in pindrow fir (Abies pindrow) along its altitudinal gradient in the Himalaya. The stages of xylem phenology, and the duration and rate of wood formation were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
2
4
0
1
Order By: Relevance
“…Several past studies reported that intra-annual xylem formation follows a sigmoid curve [32,33,36,37,48,49,53,62,73]. This intra-annual dynamics of wood-formation was confirmed as well in our study of coniferous tree species growing at a subalpine site in the Republic of Korea.…”
Section: Intra-annual Variations Of the Number Of Cells In The Cambiusupporting
confidence: 89%
See 4 more Smart Citations
“…Several past studies reported that intra-annual xylem formation follows a sigmoid curve [32,33,36,37,48,49,53,62,73]. This intra-annual dynamics of wood-formation was confirmed as well in our study of coniferous tree species growing at a subalpine site in the Republic of Korea.…”
Section: Intra-annual Variations Of the Number Of Cells In The Cambiusupporting
confidence: 89%
“…Republic of Korea was observed around 1-4 weeks later than the initiation of the cambial activity. Such restricted time delay was also reported for conifers at high altitudes [33,48,71].…”
Section: Intra-annual Variations Of the Number Of Cells In The Cambiusupporting
confidence: 76%
See 3 more Smart Citations